We are given a function $$f(x)=4\arcsin(\sqrt{x})+2\arcsin(\sqrt{1-x})$$ The derivative of $f$ is: $$f'(x)=\frac{1}{\sqrt{x-x^2}}$$ I would like to find the maximum value of $f^{-1}$. I think I have a solution, although I am not sure.


We know that $$\frac{d}{dx} f^{-1}(x)=\frac{1}{f'(f^{-1}(x))}$$ In the problem, we are to find when $$\frac{d}{dx} f^{-1}(x) =0$$ Thus, $$\frac{d}{dx} f^{-1}(x)= \frac{1}{\frac{1}{\sqrt{y-y^2}}}= \sqrt{y-y^2} = y(1-y)$$ It follows that $y=0$ or $y=1$, when the above expression is set to zero.


I assume that since the inverse function gets us back to the original value, we can write this as $f(y)=x$. Is the solution I got above the maximum value or simply the point $x$ that I have to plug into $f^{-1}$ to get the maximum value?


Let $\arcsin\sqrt x=u\implies\sin u=\sqrt x\ge0\implies0\le u\le\dfrac\pi2$

$\implies\cos u=+\sqrt{1-x}$

$\implies\arcsin\sqrt{1-x}=\arcsin(\cos u)$ $=\arcsin\left[\sin\left(\dfrac\pi2-u\right)\right]=\dfrac\pi2-u$

$$\implies f(x)=4u+2\left(\dfrac\pi2-u\right)=\pi+2\arcsin\sqrt x$$

If $y=f(x),f^{-1}(y)=x$

and $y=\pi+2\arcsin\sqrt x\implies-\arcsin\sqrt x=\dfrac\pi2-\dfrac y2$

$\sin\left(-\arcsin\sqrt x\right)=\sin\left(\dfrac\pi2-\dfrac y2\right)$

$-\sin\left(\arcsin\sqrt x\right)=\cos\dfrac y2$

$\implies-\sqrt x=\cos\dfrac y2\implies x=\cos^2\dfrac y2$

$\implies f^{-1}(y)=x=\cos^2\dfrac y2$

$\implies f^{-1}(x)=\cos^2\dfrac x2=\dfrac{1+\cos x}2$

  • $\begingroup$ is the maximum value of $f^{-1}$ 1? $\endgroup$ – Artem Nov 17 '14 at 16:08
  • 1
    $\begingroup$ @Artem, What is $f^{-1}(x)?$ In my calculation, $$f^{-1}(x)=\cos^2\frac x2$$ $\endgroup$ – lab bhattacharjee Nov 17 '14 at 16:09
  • $\begingroup$ it's the inverse of $f$. $\endgroup$ – Artem Nov 17 '14 at 16:11
  • 1
    $\begingroup$ @Artem, That's obvious. Have you calculated $f^{-1}(x)?$ $\endgroup$ – lab bhattacharjee Nov 17 '14 at 16:12
  • $\begingroup$ Since I only need the maximum value of $f^{-1}$, and I knew the $f$ and $f'$, I wanted to use that information to find the maximum point using the relationship in the solution. $\endgroup$ – Artem Nov 17 '14 at 16:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.